Education on Adequate Body Fluids for Elementary School Students - Annisa, Rifa; Hasanah, Uswatul; Moely, Cut Mulyana; Santoso, Fazila Septiani; Shafira, Ananda Dwi; Alvionita, Elsti; Amnamuchlisah, Dira; Hasibuan, Rapotan (AMK : Abdi Masyarakat UIKA, 2024)
School-aged children need to consume a lot of fluids because of their high activity levels. The habit of not consuming enough water in children can have a very negative impact on their health and development. Mild dehydration will cause fatigue, headaches and constipation. The habit of not consuming water can be a problem, especially if children tend to prioritize consuming or drinking drinks made from soda and caffeine because it can increase health risk factors from consuming these substances. To overcome this, good anticipation is needed regarding fluid deficiency in children. Prevent dehydration in school-age children by providing education on adequate body fluids for elementary school students at SD Negeri 101827 Tuntungan so they can change unhealthy drinking habits. Methods for implementing activities include health education, lectures, and carrying out pre-test and post-test activities. The post-test results of 10 questions aimed at grade 5 students showed an increase in the percentage of correct answers almost entirely compared to the results of the pre-test. Recommendations for follow-up after this activity are that the school can collaborate with the student's parents regarding accompanying students to ensure sufficient water consumption while at home.